2018
DOI: 10.1007/s10517-018-4215-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mesenchymal Stromal Cells and Conditioned Media on Healing of Skin Wound

Abstract: We studied the effect of mesenchymal stromal cells and conditioned media on healing of full-thickness skin wound in rats. Cell transplantation to the wound bed did not accelerate wound closing and had no effect on the severity of inflammation, but increased vasculariza - tion of the granulation tissue in 14 days after injury. After injection of conditioned medium to the wound, less pronounced inflammation or enhanced epithelialization was observed. The angiogenic effect was observed only after repeated adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 10 publications
0
22
0
1
Order By: Relevance
“…Accordingly, the latest study by Joseph et al also found that MSC-CM can be used to improve the quality of wound healing with minimal scar formation [2]. Using CM from MSC culture increases fibroblast and basal cell proliferation, collagen synthesis, and improve vascularization in the process of skin wound healing [9,11].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Accordingly, the latest study by Joseph et al also found that MSC-CM can be used to improve the quality of wound healing with minimal scar formation [2]. Using CM from MSC culture increases fibroblast and basal cell proliferation, collagen synthesis, and improve vascularization in the process of skin wound healing [9,11].…”
Section: Discussionmentioning
confidence: 99%
“…For the above-mentioned reason, paracrine factors such as cytokines, chemokines, and growth factors secreted by the MSC into the medium may play a key role in activating and stimulating fibroblast proliferation during the wound healing as well as regulating human hair growth [34]. It has been known that vascular endothelial growth factor (VEGF), epidermal growth factor (EGF), fibroblast growth factor (FGF), keratinocyte growth factor (KGF), angiopoietin-1, erythropoietin, and stromal-derived factor-1 (SDF-1) escalated dermal and epidermal cell proliferation and promoted migration of dermal fibroblasts [9,24,35]. Furthermore, these growth factors can enhance angiogenesis and the re-epithelialization process, which might be important to stimulate hair follicle regeneration and maintain hair-inducing activity in vivo [35,36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En este estudio, los análisis histopatológicos iniciales para ambos casos, mostraron procesos inflamatorios crónicos como microangiopatía y zonas de fibrosis y necrosis (típico de dichas lesiones) [54][55][56] ; sin embargo, a partir del tratamiento con las CTM fue posible apreciar en los dos casos una disminución de la cantidad de linfocitos infiltrantes, que se relaciona a la capacidad inmunomoduladora de las células mesenquimales en presencia de ambientes inflamatorios crónicos, permitiendo así la regeneración de piel [41,52,54] . Lo anterior conlleva a un incremento en la cantidad y calidad de vasos sanguíneos formados [57,58] , los cuales también fueron observados en los cortes histológicos de las pacientes con tratamiento. El efecto que se mostró a corto plazo al aplicar las CTM-GW sobre el cierre de las heridas crónicas, concuerda con los resultados de Navone (2014) [59] quien utilizó un andamio de fibroína y CTM, donde la herida se reduce en un 40%.…”
Section: Discussionunclassified